ChemInform Abstract: Palladium‐Catalyzed Zinc‐Amide‐Mediated C—H Arylation of Fluoroarenes and Heteroarenes with Aryl Sulfides. Issue 10 (February 2016) - Otsuka, Shinya; Yorimitsu, Hideki; Osuka, Atsuhiro
Abstract: The reaction has a broad substrate scope and tolerates multiple functional groups such as tosyloxy, trimethylsilyl, and pinacolatoboryl groups.